Techniques of memorizing quran: a study of Azhari curriculum students - Amalina Ulya, binti Abdul Jalil. (Universiti Malaysia Sarawak (UNIMAS), 2015)
The aim of this research is to identify the techniques of memorizing Quran among Azhari curriculum students at SM Islam AI-Masriyah. This research also conducted to discovers the patterns of Quran memorizing among students, preferences techniques of Quran memorizing among students and the relationship between memorization techniques and amount of surah memorized among SM Islam AI-Masriyah students, Penang. Significant correlations between each memorization techniques were also examined. Ninety one fonn four students and form five students were involved in this research. A set of questionnaires comprising ofthree parts is used in thjs research. The first part contains the respondent's demographic information such as gender, year of study, place of stay and the period they began memorizing Quran. The second part contains question related to their memorization patterns consist of time they spend per day to memorize, amount ofverse usually reported to the instructor once a week and amount of surah they memorized. The third part consists of33 items that indicates their preferences memorization techniques. Descriptive analysis is carried out to all three sections to ful til the objectives of study. Results from descriptive statistic shown students of SM Islam AI-Masriyah students have a moderate performance in terms of their time spent per day to memorize, moderate performance of amount of reported verses to their instructors and quite good achievements in amount of memorized surah. The Pearson correlation test is conducted to determine the relationship between memorization techniques and amount of surah memorized. The results of Pearson correlation test shows that most of the techniques have a positive correlation with amount of surah the student memorized.